Ni–Cr–Al Alloy for neutron scattering at high pressures. Issue 9 (12th June 2020) - Cheng, Yao; Brenk, Janik; Friedrich, Bernd; Perßon, Jörg; Maraytta, Nour; Gibson, James S. K.-L.; Korte-Kerzel, Sandra; Roth, Georg; Su, Yixi; Zhu, Fengfeng; Paulmann, Carsten; Grzechnik, Andrzej
ABSTRACT: High-pressure devices used in neutron scattering require materials with high strength, low neutron attenuation, and no activation. They should also be non-magnetic. Only very few materials fulfil these criteria. Here, it is reported on the manufacture and properties of the Ni–Cr–Al alloy (57.0 wt-% Ni, 40.0 wt-% Cr, and 3.0 wt-% Al). The casting and heat treatment to obtain the material with the optimal yield strength are described in detail. Synchrotron powder diffraction reveals that phases of the Ni2 Cr, Cr, and Ni3 Al types are present. Aging has no significant effect on their lattice parameters and volume fractions. The alloy has no magnetic order down to at least 1.9 K as evidenced by magnetic measurements and diffraction with polarised neutrons. This paper is part of a Thematic Issue on The Crystallographic Aspects of Metallic Alloys.